Ultrafast charge separation driven by differential particle and hole mobilities - Dutoi, Anthony; Wormit, Michael; Cederbaum, Lorenz S. (The journal of chemical physics, 2011)
The process of a local excitation evolving into an intramolecular charge-separated state is followed and compared for several systems by directly simulating the time propagation of the electronic wavefunction. The wavefunction and Hamiltonian are handled using the extended second-order algebraic diagrammatic construction (ADC(2)-x), which explicitly accounts for electron correlation in the dynamic many-particle state. The details of the charge separation can be manipulated according to the chemical composition of the system; atoms which dope the conjugated system with either particles or holes are shown to effect whether the particle or hole is more mobile. Initially, the charges oscillate between the ends of linear molecules (with different rates), separating periodically, but, at long times, both charges tend to spread over the whole molecule. Charge separation is also shown to occur for asymmetric systems, where it may eventually be experimentally feasible to excite a localized resonance (nonstationary state) on one end of the molecule preferentially and follow the ensuing dynamics.
Gesehen am 31.03.2022